Parametric Investigation in Malaysian Separate Sewer Systems - Hiew, Thong Yap; Ngien, S. K.; Norasman, Othman; Nadiatul Adilah, Ahmad Abdul Ghani; Norhan, Abd. Rahman (ICE Publishing, 2017)
Flow characteristics are significant in the design of sewerage systems in that poor analysis of the flow design parameters may influence the capacity of a sewerage system, causing health and environmental problems. The aim of this study is to verify the design parameters in the peak flow factor equation in Malaysian Standard Code of Practice MS 1228:1991. Data collection was conducted in a residential area at Taman Lepar Hilir Saujana, Kuantan, Pahang. ISCO 2150 Area Velocity Flow Meter and ISCO 674 Rain Gauge were used in this study to collect flow rate and rainfall intensity data, respectively. The resultant analysis shows that the flow design parameters, per capita flow and design criterion, were unexpectedly 42·2 and 16% lower than the value of per capita flow and design criterion described in MS 1228:1991, respectively. This indicates that the separate sewer systems in Malaysia may be overdesigned if using the flow design parameters recommended in MS 1228:1991. Thus, a revision of the flow design parameters may be necessary, taking into account the rising cost of materials around the world.